PEMODELAN BADAI GEOMAGNET BERDASARKAN MODEL WINDMI AKIBAT ANGIN MATAHARI - Suhayat, Sunika
Geomagnetic storm is a large-scale disturbances in the Earth's magnetic field that serve as representations of space weather. Various efforts have been made to prevent and reduce the impact of geomagnetic storms caused by extreme space weather, one of which is to predict the scale of disturbances that will occur on Earth. Geomagnetic storm prediction requires sufficient realtime observation data as an input provider and a numerical model that can project current conditions into the future as the main element. Various geomagnetic storm models have been proposed. One of the geomagnetic storm models that is constantly undergoing development is WINDMI, which is a model of low-dimensional solar wind energy transfer through the magnetosphere to the ionosphere. This model is able to predict the intensity of geomagnetic storms by producing a geomagnetic disturbance index in the form of AL and Dst. This Final Project discusses the prediction of weak (Dst <-50 nT), medium (Dst <-100 nT), and strong (Dst <-200 nT) storm models in the 24th solar cycle that best fits the observations based on the WINDMI model. The cause of each geomagnetic storm originating from solar eruptive phenomena is determined by means of solar wind plasma parameters and interplanetary magnetic fields using descriptive analysis.